Translating teamwork behaviours from aviation to healthcare: development of behavioural markers for neonatal resuscitation - Thomas, E (BMJ Group, 2004)
Improving teamwork in healthcare may help reduce and manage errors. This paper takes a step toward that goal by (1) proposing a set of teamwork behaviours, or behavioural markers, for neonatal resuscitation; (2) presenting a data form for recording observations about these markers; and (3) comparing and contrasting different sets of teamwork behaviours that have been developed for healthcare. Data from focus groups of neonatal providers, surveys, and video recordings of neonatal resuscitations were used to identify some new teamwork behaviours, to translate existing aviation team behaviours to this setting, and to develop a data collection form. This behavioural marker audit form for neonatal resuscitation lists and defines 10 markers that describe specific, observable behaviours seen during the resuscitation of newborn infants. These markers are compared with those developed by other groups. Future research should determine the relations among these behaviours and errors, and test their usefulness in measuring the impact of team training interventions.